Birds of a eucalyptus woodlot in interior São Paulo. - Willis, E. O. (FapUNIFESP (SciELO), 2003)
Some 255 birds were recorded between 1982-2001 in and near a 2314-ha Horto of old eucalyptus plantations with native understory and a lake, near Rio Claro, in central São Paulo, Brazil. This is close to the 263 recorded in and around a ten-times smaller nearby 230-ha woodlot of semideciduous forest. Different species were 44, for a total of 307 in both areas. One hundred and fifty nonvagrant forest and border species were recorded in 1982-86, a number close to the 152 in the small native woodlot. With dry years and logging of plots in 1985-93, 21 of the 150 species were lost, 42 species decreased in numbers, 49 were stable, 19 increased (15 being border species), and 5 entered (one of dry forest and 4 of borders), so 129 species remained in 1996-2001 compared to 133 in the native woodlot. Open-area birds were 33, versus 50 in better-checked grassy swales in sugar cane near the natural woodlot, for a total of 53. Several species, like some border ones, did not enter the open but isolated and mowed interior lake area, or took years to do so. Water and marsh birds were 46 versus 40 in smaller creeks and ponds near the natural woodlot (total, 55) but many were migrants or infrequent visitors using distant areas, and perhaps should be counted as 0.1-0.9 local species rather than 1 species. Use of this more accurate method would reduce waterbird totals by 14 species in the Horto and by 11 around the native woodlot. I also recommend longer censusing at the edges in large woodlots or many edge species will be recorded only in small fragments of habitat. Several species increased and others decreased with occasional cat-tail and water-lily cleanups at the lake. A forested corridor between the Horto and natural woodlot is recommended, with old eucalyptus left to provide flowers for hummingbirds.
Keywords: animal; bird; Brazil; classification; environment; Eucalyptus; population density; population dynamics; Animals; Birds; Environment; Population Density; Population Dynamics